THE EFFECTIVENESS OF QUIPPER SCHOOL-BASED E-LEARNING ON STUDENT ACCOUNTING LEARNING OUTCOMES - Sidabutar, Marta Juliati; Sidabutar, Natalia Ayu Lestari (International Conference on Humanity Education and Society (ICHES), 2024)
This research aims to determine the effectiveness of the Quipper School application on accounting learning outcomes at SMA W.R. Supratman 2 Medan. This research uses an experimental method. Sampling in this research was carried out using random sampling. The research subjects were all students of class XI IPS SMA W.R. Supratman 2 Medan, totaling 96 people. The instruments used were interviews and tests. The test is in the form of multiple choices, totaling 20 questions, and is carried out with a pre-test and post-test. The results show that the average value and learning outcomes of the experimental class using the Quipper School application are higher than those of the control class, which does not use the Quipper School application. Based on hypothesis testing using the SPSS version 20 program, the value obtained was Sig tailed = 0.003 with a significant level (α = 0.05).